SYSTEMIC ENZYME THERAPY IN COMPLEX TREATMENT OF PATIENTS WITH SEVERE BRONCHIAL ASTHMA - E. V. Churyukina; L. P. Sizyakina (Медицинская иммунология, 2019)
The paper presents the results of the study of the effectiveness and safety of the use of systemic enzyme therapy with Wobenzym in the complex treatment of patients with hormone-dependent severe bronchial asthma. It was found that the inclusion in the complex basic therapy of severe hormone-dependent bronchial asthma systemic enzyme Wobenzyme accompanied by improving the parameters of the functional state of the bronchi, reducing circulating immune complexes, a steady increase in cortisol levels. The data obtained convince of the safety of the inclusion of the preparation of systemic enzyme therapy in the complex treatment of patients with severe hormone-dependent bronchial asthma, improving the effectiveness of basic therapy, improving control over the course of the disease, allow to develop indications for the appointment of Wobenzyme patients with severe bronchial asthma.